EVALUATION OF VOLLEYBALL SKILLS AMONG FEMALE STUDENTS OF STATE SENIOR HIGH SCHOOL 1 RIKIT GAIB, GAYO LUES DISTRICT - Lidia Anita Sari; Munzir; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Based on the observations the researchers made in January 2023 atSMA Negeri 1 Rikit Gaib, Gayo Lues Regency, the researchers foundseveral conditions related to volleyball extracurricular activities at theschool. The women's volleyball team for SMA Negeri 1 Rikit Gaib inrecent years has been one of the top teams in the championships heldby the Regional Government of Gayo Lues Regency where this teamhas always been the team that enters the semifinals. However, for thepast two years, especially after the Covid-19 pandemic, the women'svolleyball team at SMA Negeri 1 Rikit Gaib has always had to admitdefeat to the opposing team in the preliminaries and was knocked outof the game. This study aims to find out how the ability to play volleyballfor female students at SMA Negeri 1 Rikit Gaib, Gayo Lues Regency.The population in this study were all female students at SMA Negeri 1Rikit Gaib, Gayo Lues Regency, participating in volleyballextracurricular activities in 2023, totaling 15 people. The sample in thisstudy was 15 students from SMA Negeri 1 Rikit Gaib, Gayo LuesRegency in 2023, which were taken using a total sampling approach.The data in this study were collected by means of tests andmeasurements of the basic skills of playing volleyball. The data analysistechnique used was carried out using simple statistical analysis techniques using the average and percentage approaches. The resultsof the study found that: 1) the average ability to serve volleyball in SMANegeri 1 Rikit Gaib was in the good category with an average score of25.4, 2) the average passing ability in volleyball at SMA Negeri 1 Rikitoccult is in the less category with an average value of lower passingability of 23, 3) the average passing ability of volleyball in SMA Negeri1 Rikit occult is in the very poor category with an average value ofupper passing ability of 13, and4) the average ability to smash volleyball at SMA Negeri1 Rikit Gaib is in the less category with an average scoreof upper passing ability of 25.